Turning Intentions into Animal Welfare Improvement in the Asian Livestock Sector. Issue 4 (2nd October 2019) - Sinclair, Michelle; Morton, John; Phillips, Clive J. C.
ABSTRACT: Intentions form the basis of behavioral action to improve animal welfare; however an intention-behavior gap has been previously identified. Livestock stakeholders in China, Malaysia, Vietnam and Thailand (n = 1041) involved in slaughter and transport completed a survey in which they were asked their level of intention to improve animal welfare, and their level of confidence in their ability to do this. Chinese respondents had the most confidence in their ability to improve animal welfare, and veterinarians showed more confidence than livestock team leaders. Those with high or low intentions, and either high or low confidences were compared for key influencing factors to identify the circumstances that may be most conducive to behavior change. Respondents with high intentions and low confidence in their ability to improve animal welfare identified extrinsic factors associated with their immediate workplace and different company priorities, and the intrinsic factor of lack of personal knowledge. It is concluded that targeting these areas to improve confidence in stakeholders in livestock transport and slaughter could bring the most improvements in animal welfare initiatives.